Online reservation systems in e-Business: Analyzing decision making in e-Tourism - Constantinos Halkiopoulos; Hera Antonopoulou; Dimitrios Papadopoulos; Ioanna Giannoukou; Evgenia Gkintoni (Journal of Tourism, Heritage & Services Marketing, 2020)
Tourism is one of the fastest growing industries worldwide and in general, the Internet continues to gain importance in the tourism sector. The study focuses on exploration of knowledge of online booking systems and on the views of local students-users concerning the booking rate based on these online systems. Another perspective of this project is to investigate the decision-making process (emotion-focused) that they follow in order to choose a tourist destination via online booking systems. For the purposes of this study, three scales were administered E-WOM and Accommodation Scale, Emotion-Based Decision-Making Scale and Trait Emotional Intelligence Scale. Then, survey data were collected, preprocessed and analyzed based on Data Mining techniques evaluating the results. More specifically, classification and association algorithms were utilized to manage to describe hidden patterns. E-Tourism will continue to be oriented towards the consumers and the technology that surrounds them, providing dynamic communication in electronic business.
Keywords: D7; L81; L83; 330; Online Booking Systems; e-Tourism; Hotel Selection Factors; Expert System